Al-Qur’an and Social Disability: Study Dilthey’s Hermeneutics - Hafiz Syed Husain; Shinta Nurani (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
Disability is a very complex issue and probably can influence various aspects in community life. Persons with disabilities are often hard to maintain the interaction between the limitation of individual function and the problems in their environment due to the negative attitude and stigma by discriminative people toward persons with disabilities. Besides, religion and normativity rules are very attentive and respect them (persons with disabilities). Inclusive education is effective and essential for persons with disabilities, but the modification of curriculum in class cannot meet their education rights relating to the social life as it should. The research method used is analytical descriptive in order to observe the possibility of hermeneutics towards the criticism of positivism as the dominant theme in research of social sciences, arts, and humanities. This paper relates to the disability social activities termed as social disability coming from the interpretation of Quran and social reality that then emerge the precious understanding and life experience for persons with disabilities so that it gives positive impact for students with disability, no disability, family, and large community.